EFFECT OF GERMINATION OR HEAT TREATMENT OF FENUGREEK SEEDS ON GROWTH AND SOME CARCASS CHARACTERISTICS OF AWASSI LAMBS - Baidaa Ghanim; Omar Almallah; Mohammed Ibrahem (Mesopotamia Journal of Agriculture)
The study used 20 Awassi lambs with an average weight of 25.65 ± 3.29 kg and ages between 4-5 months. The lambs in all groups were fed the basal diet without any additives in the first group (control). In the second group, lambs were fed a basal diet in addition to 30 g/lamb of raw fenugreek seeds (RF); in the third and fourth groups, lambs were fed a basal diet with heat-treated (HF) and germinated seeds (GF). The results showed insignificant differences in final body weight and daily gain, feed efficiency was lowered in all fenugreek treatments as compared control, the lambs fed with (HF) had better feed efficiency within fenugreek treatments. Dressing percentage was higher (P≤0.05) in GF (52.47%) as compared to control (49.32%) and RF (48.98%). Back fat thickness decreased in all fenugreek treatments compared to the control. Tail and total fat were not affected significantly with treatments. Fat percent in ribs 9-10-11 was higher (P≤0.05) in RF and HF groups (35.19 and 32.15%) as compared with control (25.32%), while the value in GF (27.32%) was close to the control. In addition, germination and heat treatments of fenugreek seeds led to an alteration in chemical composition and change in bioactive compounds compared to raw seeds. The most critical change observed is the decrease in oxalate compounds in the heat-treated fenugreek compared to other treatments. In conclusion, fenugreek seeds in 30 g/lamb daily had a detrimental effect on productive performance, and treated with heat or germination reduced the adverse impact of raw seeds.